The role of slip transfer at grain boundaries in the propagation of microstructurally short fatigue cracks in Ni-based superalloys. (15th March 2019) - Jiménez, M.; Ludwig, W.; Gonzalez, D.; Molina-Aldareguia, J.M.
Abstract: Crack initiation and propagation under high-cycle fatigue conditions have been investigated for a polycrystalline Ni-based superalloy by in-situ synchrotron assisted diffraction and phase contrast tomography. The cracks nucleated along the longest coherent twin boundaries pre-existing on the specimen surface, that were well oriented for slip and that presented a large elastic incompatibility across them. Moreover, the propagation of microstructurally short cracks was found to be determined by the easy slip transfer paths across the pre-existing grain boundaries. This information can only be obtained by characterization techniques like the ones presented here that provide the full set of 3D microstructural information. Graphical Abstract: